ICT (Information and Communication Technology) marketing of Link3 Technologies Ltd.: a concept of marketing strategy - Hossain, Asif (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2016.